Understanding macro developments in environmental public opinion - Radford-Kirby, M (2022)
This thesis examines macro developments in environmental public opinion to not only discern the patterns and driving factors of these changes, but to also investigate the potential consequences of such. Given the lack of climate opinion data, it first examines existing temporal measures of cross-national climate concern, and how well these align across survey organisations. As the attention given to the environment by the public has fluctuated over time, a British-focused investigation then examines how monthly changes in public salience between 2006-2019 may be linked to agenda-setting forces including media coverage, parliamentary debate, environmental protest, as well as other exogenous factors. Considering the surge in green party support in the 2021 German elections, this theoretical approach is then extended to examine changing green support in Germany between 1994-2019.